Seed-Borne Erwinia persicina Affects the Growth and Physiology of Alfalfa (Medicago sativa L.) - Yao, Bo; Huang, Rong; Zhang, Zhenfen; Shi, Shangli (Frontiers in Microbiology, 2022)
Seed-borne Erwinia persicina can be transmitted globally via alfalfa (Medicago sativa L.) seed trade, but there is limited information about the impact of this plant-pathogenic bacterium on alfalfa plants. In this study, strain Cp2, isolated from alfalfa seeds, was confirmed by whole-genome sequencing to belong to E. persicina. Subsequently, the effects of Cp2 on alfalfa growth and physiology were evaluated by constructing a rhizosphere infection model. Strain Cp2 had a strong inhibitory effect on the elongation and growth of alfalfa roots, which was very unfavorable to these perennial plants. Furthermore, an increased number of leaf spots and yellowing symptoms were observed in plants of the Cp2 group from day 10 to day 21 and the strain Cp2 was re-isolated from these leaves. Correlation between growth and photosynthetic parameters was analyzed and the significant decreases in fresh weight and root and plant lengths in the Cp2 group were related to the marked reduction of chlorophyll b, carotenoid, transpiration rate, and stomatal conductance of leaves (r > 0.75). In addition, nine physiological indicators of root, stem, and leaf were measured in the plants 21 days after treatment with Cp2. The physiological response of root and leaf to Cp2 treatment was stronger than that of stem. The physiological indicators with the greatest response to Cp2 infection were further explored through principal component analysis, and superoxide dismutase, peroxidase, ascorbate peroxidase, and soluble protein showed the greatest changes in roots, stems, and leaves (P < 0.001). Among tissues, the commonality was the change of soluble protein. Therefore, soluble protein is speculated to be a physiological marker during alfalfa–E. persicina interactions. These findings indicate that once E. persicina spreads from alfalfa seeds to the rhizosphere, it can invade alfalfa roots and cause disease. This study demonstrates that this plant pathogenic bacterium may be a potential threat to new environment when they spread via seed trade and these “dangerous hitchhikers” warrant further attention, especially in the study of bacterial diseases in pasture-based production systems.